Toward Economic Legal Pluralism in Indonesia’s Mining Law: Sadd al-Żarī’ah or Fatḥ al-Żarī’ah? - Nashirulhaq, Muhammad; Idzharul Haq, Kukuh Prasetyo (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2025)
Abstract: The dominance of fiscal and investment interests in Indonesia’s mining regime indicates the need for a renewed interpretation based on economic legal pluralism. This article examines how Law No. 4 of 2009 jo No. 3 of 2020 on Mineral and Coal Mining and the Job Creation Law shape the flow of state and corporate profits while marginalizing Indigenous Peoples from fair benefit-sharing schemes. The perspective of economic legal pluralism is applied to analyze the interaction among state law, corporate practices represented by IUP and IUPK, and customary law including hak ulayat as a single field of distribution. The concepts of sadd al-żarī‘ah and fatḥ al-żarī‘ah are used as analytical instruments to assess the prevention of mafsadah (harms) and the realization of maṣlaḥah at the community level. The findings show the closure of substantive participation channels through the simplification of environmental impact assessments and public consultations, the predominance of CSR-based compensation over rights-based claims, and the absence of measurable benefit-sharing mechanisms. The theoretical contribution lies in an evaluative framework that connects the principle of distributive justice in Islamic business law with auditable legal and institutional indicators. Policy implications include stronger recognition of hak ulayat in licensing, verifiable FPIC mechanisms, community quotas in revenue-sharing funds, citizen-based monitoring, and effective grievance procedures. The study is limited by its focus on national regulations and the absence of quantitative measurement of rent flows. Future research should expand fieldwork and regional comparisons to test the effectiveness of these designs.   Abstrak: Dominasi kepentingan fiskal dan investasi dalam rezim pertambangan menandakan kebutuhan pembacaan ulang berbasis pluralisme hukum ekonomi. Kajian dalam artikel ini mengajukan rumusan masalah utama tentang bagaimana UU Minerba No. 4/2009 jo. UU No. 3/2020 dan UU Cipta Kerja membentuk aliran keuntungan negara-korporasi sekaligus meminggirkan masyarakat adat dari skema bagi hasil yang adil. Perspektif pluralisme hukum ekonomi digunakan untuk membaca interaksi hukum negara, praktik korporasi (IUP/IUPK), dan hukum adat (termasuk hak ulayat) sebagai satu ruang distribusi, sementara sadd aż-żarī‘ah dan fatḥ aż-żarī‘ah dioperasionalkan sebagai instrumen analitis untuk menakar pencegahan mafsadat serta pembukaan maṣlaḥah pada tingkat komunitas. Temuan utama menunjukkan penutupan kanal partisipasi substantif melalui penyederhanaan AMDAL dan konsultasi publik, dominannya kompensasi CSR dibanding klaim berbasis hak, serta absennya mekanisme benefit-sharing yang terukur. Kontribusi teoretis hadir pada perumusan kerangka evaluatif yang menautkan asas keadilan distributif dalam hukum bisnis Islam dengan indikator legal-institusional yang dapat diaudit. Implikasi kebijakan meliputi penguatan pengakuan hak ulayat dalam perizinan, penegakan FPIC yang dapat diverifikasi, kuota komunitas dalam DBH, pemantauan berbasis warga, dan jalur keberatan yang efektif. Keterbatasan riset terletak pada fokus regulasi nasional serta belum digunakannya pengukuran kuantitatif aliran rente; riset lanjut disarankan memperluas studi lapangan dan perbandingan regional untuk menguji efektivitas rancangan tersebut.